G protein-coupled receptors in the hypothalamic paraventricular and supraoptic nuclei – serpentine gateways to neuroendocrine homeostasis - Hazell, Georgina G.J. (Academic Press, 2012)
G protein-coupled receptors (GPCRs) are the largest family of transmembrane receptors in the mammalian genome. They are activated by a multitude of different ligands that elicit rapid intracellular responses to regulate cell function. Unsurprisingly, a large proportion of therapeutic agents target these receptors. The paraventricular nucleus (PVN) and supraoptic nucleus (SON) of the hypothalamus are important mediators in homeostatic control. Many modulators of PVN/SON activity, including neurotransmitters and hormones act via GPCRs – in fact over 100 non-chemosensory GPCRs have been detected in either the PVN or SON. This review provides a comprehensive summary of the expression of GPCRs within the PVN/SON, including data from recent transcriptomic studies that potentially expand the repertoire of GPCRs that may have functional roles in these hypothalamic nuclei. We also present some aspects of the regulation and known roles of GPCRs in PVN/SON, which are likely complemented by the activity of ‘orphan’ GPCRs.